Are Revisions of Patellofemoral Arthroplasties More Like Primary or Revision TKAs. Issue 1 (January 2015) - Parratte, Sébastien; Lunebourg, Alexandre; Ollivier, Matthieu; Abdel, Matthew P.; Argenson, Jean‐Noël A.
Abstract: Background: Patellofemoral arthroplasty (PFA) can be considered in patients with patellofemoral disease. However, the use of partial arthroplasty often causes concern among clinicians and patients that revision to total knee arthroplasty (TKA) will be needed and, if so, whether this revision will be straightforward or more complicated. Questions/purposes: We set out to determine if conversion of a PFA to a TKA was more similar to a primary or to a revision TKA in terms of surgical characteristics, knee scores, range of motion, and complications. Methods: Between 2001 and 2008, we revised 21 PFAs to TKAs, all of which were available for followup at a minimum of 5 years (median, 6 years; range, 5‐12 years). These patients were matched one‐to‐one by age, sex, body mass index, length of followup, and preoperative Knee Society Scores (KSS) to 21 primary and 21 revision TKAs. We analyzed operative time and amount of blood loss. Clinical outcomes assessed were range of motion and KSS. Results: Blood loss (405 mL versus 460 mL versus 900 mL; odds/hazard ratio, 1.33, 95% confidence interval [CI], 0.3‐5.85; p = 0.14 for primary TKA versus revision PFA and odds/hazard ratio, 0.13, 95% CI, 0.03‐0.52; p < 0.01 for revision PFA versus revision TKA) and operative time (52 minutes versus 72 minutes versus 115 minutes; odds/hazard ratio, 5.45, 95% CI, 1.23‐27.4; p = 0.02 for primary TKA versus revision PFA and odds/hazard ratio, 0.5, 95% CI, 0.01‐0.44; p < 0.001 for revision PFA versus revision TKA) were not different between the primary TKA and revision PFA groups but higher in the revision TKA group. KSS (knee and function) were higher in the primary TKA group (92 [range, 60‐100] and 91 [range, 65‐100]) than they were in the revision PFA (85 [range, 40‐100] and 85 [range, 30‐100]) and revision TKA groups (75 [range, 30‐100] and 68 [range, 25‐100]; p < 0.001). Flexion was better in the primary TKA (125 [range, 105‐130]) and revised PFA (120 [range, 100‐130]) groups than the revision TKA group (105 [range, 80‐115]; p = 0.0013). There were more complications in the revision PFA group (two of 21) compared with the primary TKA group (zero of 21, p = 0.005) but not compared with the revision TKA group (three of 21; p = 0.85). Conclusions: With the numbers available, we found that revising a PFA is comparable to a primary TKA in regard to surgical characteristics and postoperative clinical outcomes (including knee scores and range of motion), and both are superior to revision TKA, although the frequency of complications was higher in the revision PFA group than it was in the primary TKA group. The majority of patients undergoing revision of a PFA to a TKA can be treated with a standard implant. Level of Evidence: Level III, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.